Partnership Strategy, Early Childhood Education - Muhammad Noor (Tajdid Al-Athfal, 2022)
Partnership is mutually beneficial cooperation between parties, by placing both parties in an equal position. Tri sentra pendidikan partnership is an effort to cooperate between educational units, families, and communities based on mutual cooperation, equality, mutual trust, mutual respect, and willingness to sacrifice in building an educational ecosystem that fosters the character and culture of student achievement. There is mutual trust, understanding, mutual transparency and openness or transparency between schools and parents, communities and certain agencies related to PAUD institutions. So as to support the level of quality and quantity of paud institutions.